Characteristics of Trauma Patients Who Died at UGM Academic Hospital (RSA UGM) - Prananingrum, Febriana; Tyas, Humaera Elphananing; Caswita, Aditya Bagas; Dewa Rachmat, Radyan Artha; Widyastuti, Rina; Lestari, Ade Febrina; Darwito, Darwito; Pratama, Yanasta Yudo (Academic Hospital Journal, 2024)
BACKGROUND : Trauma becomes the main health problem worldwide due to its high mortality rate. Traffic accidents are a trauma with a high incidence and death rate in Indonesia, specifically in Yogyakarta. Factors causing trauma-related death are the lack of hospital infrastructure, the lack of quality human resources, the lack of standardization of trauma management, and the limited number of hospitals providing comprehensive trauma services. This research aims to identify the characteristics of trauma patients who died while receiving medical treatment at UGM Academic Hospital and to analyze the mortality of patients according to the trimodal distribution to prepare this hospital to become a trauma center hospital.METHOD : This quantitative descriptive research used a cross-sectional method. Data were taken from medical records of patients admitted to the ER of UGM Academic Hospital in 2018-2023 based on predetermined inclusion and exclusion criteria. The research was conducted from March to November 2023.RESULT : This research involved 58 patients consisting of 42 (72.4%) male and 16 (27.6%) female patients. The most common cause of death was brain injury (63%), followed by spinal cord injury (13.7%), multi-organ failure and sepsis (8.6%), cardiac and respiratory arrest (6.8%), and comorbidities patients (6.8%).CONCLUSION : The majority of trauma patients who died at the UGM Academic Hospital are male and aged 60-80 years with the main cause of death of brain injury. The patient dies at the late death stage based on trimodal distribution of death time.